2017
DOI: 10.1021/acs.jpcb.7b06687
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Binding Interactions between Human RANKL and Its Decoy Receptor Osteoprotegerin

Abstract: Recent studies have revealed the importance and the active contribution of the RANKL/OPG/RANK pathway in many bone diseases including different forms of common osteoporosis. In this study, we present an extensive atomistic molecular dynamic study of the OPG/RANKL system. Within the molecular models, we varied the number of OPG molecules bound to the RANKL trimer and carried out a study to determine how the binding affinity of the OPG/RANKL system changes as a function of OPG concentration. The molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Besides binding RANK, OPG is able to interact with TRAIL and induces apoptosis of tumor cells through the cell-surface receptors death receptor 4 (DR4) and DR5 in the TNFRSF family [9]. The binding mode to RANKL was determined from computational docking and molecular dynamics simulations [10,11]. OPG is expressed in vivo by ECs, VSMCs, and osteoblasts.…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…Besides binding RANK, OPG is able to interact with TRAIL and induces apoptosis of tumor cells through the cell-surface receptors death receptor 4 (DR4) and DR5 in the TNFRSF family [9]. The binding mode to RANKL was determined from computational docking and molecular dynamics simulations [10,11]. OPG is expressed in vivo by ECs, VSMCs, and osteoblasts.…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…Os processos de osteoclastogênese e de diferenciação de osteoclastos envolvendo RANKL se iniciam com a ligação deste ao seu receptor RANK, o qual é presente na superfície de pré-osteoclastos. Enquanto isso, a OPG, solúvel no plasma, apresenta efeito antirreabsortivo, uma vez que tem alta afinidade por RANKL e impede a interação de RANK (KAPASA et al, 2017;MUNASINGHE;LIN;COLINA, 2017;CHEN et al, 2018;UDAGAWA et al, 2020).…”
Section: Osseointegração De Implantes Dentáriosunclassified
“…RANKL and OPG system: One of the main regulators of osteoclast differentiation and function is the RANKL/RANK/OPG system [20,22]. It has been suggested that circulating levels of OPG and RANKL could reflect local bone marrow production [72,73]. The activator of the nuclear factor kappa-B ligand is OPG.…”
Section: New Bone Markersmentioning
confidence: 99%